Evaluasi Usability Mobile Game Pokemon Go Menggunakan Metode Heuristic - Farandi Angesti; Eriq Muh. Adams Jonemaro; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Pokemon Go as one of the game Augmented Reality had seized the attention of millions of people of the world. Unfortunately this game left behind 12 million users because users feel less satisfied when losing their data when the application is updated. Looking at this, research using heuristic evaluations is needed to address the specific problems that exist in Pokemon Go games. So with the knowledge of the problem in the game specifically, game companies can know what to fix in the game. The heuristic evaluation used is usability heuristic method ,there are 9 aspects in that method . Based on the authors research using usability heuristic method found that there are 26 problems with different severity levels. The most problems are found in the aspects of consistency and standards and flexibility and efficiency of use. Based on the level of severity, consistency and standards occupy the medium level. Next on the level of minor severity, there are 5 heuristic namely visibility of system status, offer real world objects, error prevention, flexibility and efficiency of use, and aesthetic and minimalist design. Lastly in severity cosmetics level there are 3 heuristic that is, recognition rather than recall, help user recognize, diagnose, and recover from errors (H9). From the problems found in the principle of heuristics researchers summarize the things that make pokemon go abandoned by active users ie no explanation of changing elements or clearer notification game, the use of icons that are less informative, on the side of the gameplay there is no confirmation menu for the evolution of pokemon, many terms are still difficult to understand by the player, on the side of the gameplay more interesting on the version available in the ninebox, tutorials that are not available in the early session of the game, less familiar game instructions. From this the results of this study, the manufacturer of Pokemon Go is recommended to prioritize improvements based on the level of severity. Problems with medium severity are strongly recommended to be improved, followed by improvements in problems with minor severity and cosmetic levels.